Customised fitness function of evolutionary algorithm for optimization of car park space / Ahmad Syahir Ab. Aziz - Ab. Aziz, Ahmad Syahir (2017)
Nowadays, parking is important thing that required by place where vehicle can access. Vehicle that park at the place must safe and comfortable. Parking space are designed based on the three type which are parallel, diagonal, and perpendicular. Size of the area and the condition of the empty space are affecting the number of parking space.